Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Discover in-depth solutions to your questions from a wide range of experts on our user-friendly Q&A platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

Solve the system of equations above using it elimination write your answer in the form (x,y) 8X + Y = -16-3X + Y = -5

Sagot :

Given the system of the equation below;

[tex]\begin{gathered} 8x+y=-16----(1) \\ -3x+y=-5----(2) \end{gathered}[/tex]

We can use the elimination method to solve the systems of equations

Step 1: Subtract equation 2 from equation 1 and solve for x

[tex]\begin{gathered} 8x+y-(-3x+y)=-16-(-5) \\ 8x+y+3x-y=-16+5 \\ 11x=-11 \\ \frac{11x}{11}=-\frac{11}{11} \\ x=-1 \end{gathered}[/tex]

Step 2: Sustitute x = 1 in equation 1

[tex]\begin{gathered} 8(-1)+y=-16 \\ -8+y=-16 \\ y=-16+8 \\ y=-8 \end{gathered}[/tex]

Therefore, the solution to the system of equation is

[tex](-1,-8)[/tex]